PENGARUH INSPIRATORY MUSCLE TRAINING TERHADAP STATUS RESPIRASI PADA PENYAKIT PARU OBSTUKTIF KRONIK - WULAN SARI PURBA; ASTIKA HANDAYANI (Jurnal Ilmu Keperawatan, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic lung disease characterized air flow resistance in the airways that are progressive non-reversible or partially reversible. Pulmonary rehabilitation is a comprehensive, multidisciplinary treatment that has been shown to be beneficial for people with COPD. Inspiratory muscle training is a breathing exercise with low intensity loads to increase lung expansion and inspiratory muscle strength performed in COPD patients. The purpose of this study was to identify the effect of inspiratory muscle training on respiration status in patients with chronic obstructive pulmonary disease. The design of this study was a quasi-experimental design with a non equivalent control group design. The sample of the study was 46 patients with stable COPD who were outpatient at the Army Hospital TK IV 01.07.01 Pematangsiantar, with a total of 46 people divided into two groups, 23 people in the intervention group and 23 in the control group. The results showed that there was an effect before and after inspiratory muscle training on respiratory frequency with p = 0,014 and there was an effect before and after inspiratory muscle training on oxygen saturation p = 0,001.It can be concluded that inspiratory muscle training using incentive spirometer has been shown to reduce symptoms of shortness of breath and increase oxygen saturation in stable COPD patients.